2018
DOI: 10.17583/qre.2018.3240
|View full text |Cite
|
Sign up to set email alerts
|

Support to Children’s Education in the Urban Slums of Nairobi: Community and Parents’ Perceptions with an Expanded Phase of an Education Intervention Program

Abstract: The objective of this paper is to examine the perceptions of community elders and parents on their roles regarding support to their children’s education. Data come from the qualitative component of a baseline survey conducted in Korogocho and Viwandani, two urban informal settlements in Nairobi, Kenya. Data were collected in April-May 2016 through in-depth interviews, key informant interviews and focus group discussions. Results demonstrated that community elders internalized their role as the face of governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…In India, NGOs have tried to expand access to education by providing facilities like ballades, offering non-formal education, and helping enrol 4 students in schools (⇡Sonawat & Sikh, 2007). Elsewhere in Kenya, community leaders are influential members of their community, and NGOs used their influence to encourage parents to take a more active interest in their children's education (⇡Abuya et al, 2018).…”
Section: Accessing Education In Slum Areasmentioning
confidence: 99%
“…In India, NGOs have tried to expand access to education by providing facilities like ballades, offering non-formal education, and helping enrol 4 students in schools (⇡Sonawat & Sikh, 2007). Elsewhere in Kenya, community leaders are influential members of their community, and NGOs used their influence to encourage parents to take a more active interest in their children's education (⇡Abuya et al, 2018).…”
Section: Accessing Education In Slum Areasmentioning
confidence: 99%
“…This is in line with Chireshe (2006) who revealed that parents were more impressed by improved grades and test scores of their children because it is difficult to claim credit for improved performance on tests to school counselling. In Kenya Abuya, Wekulo & Muhia (2018) suggests that peer led groups should work with parent volunteers to enable them to see all learners seeking their help.…”
Section: Peer Led Groupsmentioning
confidence: 99%
“…Dado que todo el alumnado, ya sean niños o adolescentes, entra en contacto con el mismo programa curricular, se presuponen en ellos las mismas necesidades (Noddings, 2005) y se establecen los mismos objetivos que, además, se tratarán de observar con similares medios de evaluación (Aoki, 2012). Ya que el sistema educativo acoge a todo el alumnado de manera similar, podríamos decir que las diferencias entre historias de éxito y fracaso escolar se sitúan en el acceso al conocimiento y la cultura que tienen fuera de la escuela, fundamentalmente en los contextos familiares (Abuya, Wekulo, & Muhia, 2018).…”
Section: Estudiantes En Situación De Riesgounclassified